algebra,math

posted by .

My qustion is for the following

the problem reads as follows

(x-1)^2 = 7
x-1=+- sqrt 7
x= 1+- sqrt 7

the method they use was factoring in order to simplify the equation to make it easier is this correc?

x^2-9x-4=6
x^2-9x-10=0
(x-10)(x+1)=0

What method did they use here I think its simplifying but i am not sure?

4x^2-8x+3=5
4x^2-8x-2=0
2(2x^2-4x-1)=0
2x^2-4x-1=0

here the method that they use was first factoring then simplefiying and then they will use the quadratic formula is this correct?

You are right on all counts.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math

    how would you simplify this equation: y = (x+3)/[(4-sqrt(16+h))] please help me! you have three variables. I am not certain "simplify" is an appropriate term here. ohhhh it was my mistake. I meant: y = h/[(4-sqrt(16+h))] y = h/[(4-sqrt(16+h))] …
  2. math,algebra,help

    Directions are simplify by combining like terms. x radiacal 18 -3 radical 8x^2 can someone show me how to do these types of problems. thanks I cant determine the second term. For the first, I think you meant x sqrt(18) which reduces …
  3. Math

    How do you find a square root of a number that's not a perfect square?
  4. algebra,math,help

    Use Property 2 to simplify each of the following radical expressions. sqrt (10)/ sqrt(49) My answer: sqrt (10) / (7) THis next one i need help: Use the properties for radicals to simplify each of the following expressions. Assume that …
  5. Algebra 2: Radicals URGENT!!

    Could some kind, saintly soul help me solve this problem?
  6. Calculus - Second Order Differential Equations

    Posted by COFFEE on Monday, July 9, 2007 at 9:10pm. download mp3 free instrumental remix Solve the initial-value problem. y'' + 4y' + 6y = 0 , y(0) = 2 , y'(0) = 4 r^2+4r+6=0, r=(16 +/- Sqrt(4^2-4(1)(6)))/2(1) r=(16 +/- Sqrt(-8)) r=8 …
  7. Calculus

    Please look at my work below: Solve the initial-value problem. y'' + 4y' + 6y = 0 , y(0) = 2 , y'(0) = 4 r^2+4r+6=0, r=(16 +/- Sqrt(4^2-4(1)(6)))/2(1) r=(16 +/- Sqrt(-8)) r=8 +/- Sqrt(2)*i, alpha=8, Beta=Sqrt(2) y(0)=2, e^(8*0)*(c1*cos(0)+c2*sin(0))=c2=2 …
  8. algebra

    simplify: square root of 5 + square root of 20 - square root of 27 + square root of 147. simplify: 6/4square root of 2 sqrt 5 + sqrt 20 - sqrt 27 + sqrt 147 = sqrt 5 + sqrt (4*5) - sqrt (3*9) + sqrt (49*3) = 3 sqrt 5 - 3 sqrt 3 + 7 …
  9. Algebra 2

    Operations with Complex Numbers Simplify. 1. sqrt(-144) 2. sqrt(-64x^4) 3. sqrt(-13)*sqrt(-26) 4. (-2i)(-6i)(4i) 5. i13 6. i38 7. (5 – 2i) + (4 + 4i) 8. (3 – 4i) – (1 – 4i) 9. (3 + 4i)(3 – 4i) 10. (6 – 2i)(1 + i) 11. (4i)/(3+i) …
  10. algebra

    am I right? 1. Simplify radical expression sqrt 50 5 sqrt ^2*** 2 sqrt ^5 5 sqrt ^10 5 2. Simplify the radical expression sqrt 56x^2 28x 2x sqrt 14*** 2x sqrt 7 sqrt 14x2 3. Simplify the radical expression. sqrt 490y^5w^6 2 sqrt 135y^2

More Similar Questions